Posterior ocular parameters following extraocular muscle surgery: an optical coherence tomography study - Uzun, Aslıhan; Keleş Şahin, Asena (Journal of Surgery and Medicine, 2022)
Background/Aim: Muscle trauma, vascular injury, and compensatory vasoconstriction during strabismus surgery may cause changes in the choroidal circulation in the early postoperative period. This study aims to evaluate the effect of extraocular muscle surgery on posterior ocular parameters, including central subfield thickness (CST), average retinal thickness (ART), choroidal thickness (CT), and macular volume (MV). Methods: This prospective cohort study included 26 eyes of 26 strabismic patients who underwent single medial or lateral rectus recession surgery using a fornix-based conjunctival incision. All participants underwent detailed ophthalmologic evaluation, including axial length (AL) and spherical equivalent (SE), uncorrected (UCVA), and best-corrected visual acuity (BCVA). Retinal and choroidal images were obtained using spectral-domain optical coherence tomography (OCT). All measurements were performed preoperatively and repeated 1 week and 1 month after surgery. Results: All patients received satisfactory results in terms of deviation. None of the patients showed changes in AL, SE, UCVA, and BCVA. No significant differences were noted in CST and MV values (P=0.472 and P=0.182, respectively). Although subfoveal CT and ART showed statistically significant decreases 1 week after surgery (P=0.012 and P=0.046, respectively), no significant differences in these values were observed 1 month after surgery (P>0.05). No significant differences exist in the measurements between the preoperative, postoperative first week, and first month in nasal and temporal CT (P>0.05). Conclusion: Extraocular muscle surgery performed with the fornix-based conjunctival incision is a safe procedure for posterior ocular parameters, including CST, ART, CT, and MV.